Spatiotemporal Characterization of GPCR Activity and Function during Endosomal Trafficking Pathway - Kim, Hyunbin; Lee, Hae Nim; Choi, Jaesik; Seong, Jihye (AMER CHEMICAL SOC, 2021)
G protein-coupled receptor (GPCR) is activated by extracellular signals. After their function at plasma membrane, GPCRs are internalized to be desensitized, while emerging evidence suggests that some GPCRs maintain their activity even after internalization. The endosomal trafficking pathway of a prototypic GPCR, beta adrenergic receptor 2 (B2AR), is in the range of several hours, however, spatiotemporal B2AR activity during this long-term endosomal trafficking pathway has not been characterized yet. Here, we analyze an agonist-induced real-time B2AR activity and its downstream function at the level of individual vesicles, utilizing a fluorescence resonance energy transfer (FRET)-based B2AR biosensor and cAMP reporters tethered at different trafficking stages of endosomes. Our results report that the internalized B2ARs sustain the activity and maintain the production of cAMP for several hours during the endosomal trafficking pathway. Temporal kinetics of B2AR activity is mathematically well explained by our active-vesicle population model modified from the Ricker model. Therefore, our GPCR monitoring system and a new kinetics model can be applied to understand the spatiotemporal GPCR activity and its downstream function during the endosomal trafficking pathway.